Neurotoxicity of neem commercial formulation (Azadirachta indica A. Juss) in adult zebrafish (Danio rerio) - Bernardi, M. M. [UNESP]; Dias, S. G. [UNESP]; Barbosa, V. E. [UNESP] (Elsevier B.V., 2013)
The neurotoxic effects of a commercial formulation of Azadirachta indica A. Juss, also called neem or nim, in adult zebrafish were determined using behavioral models. General activity, anxiety-like effects, and learning and memory in a passive avoidance task were assessed after exposure to 20 or 40 mu l/L neem. The results showed that 20 mu l/L neem reduced the number of runs. Both neem concentrations increased the number of climbs to the water surface, and 40 mu l/L increased the number of tremors. In the anxiety test, the 20 mu l/L dose increased the number of entries in the light side compared with controls, but the latency to enter the dark side and the freezing behavior in this side did not changed. In relation to controls, the 40 mu l/L neem reduced the latency to enter in the light side, did not change the number of entries in this side and increased freezing behavior in the light side. In the passive avoidance test, pre-training and pre-test neem exposure to 40 mu l/L decreased the response to the learning task. Thus, no impairment was observed in this behavioral test. We conclude that neem reduced general activity and increased anxiety-like behavior but did not affect learning and memory. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Dark/light task; Fish; General activity; Anxiety; Learning and memory